2015
DOI: 10.1002/pssa.201431741
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of InGaN superluminescent diodes

Abstract: The design process of superluminescent diode has been discussed on the basis of nitride diodes with bend-waveguide geometry. The devices were fabricated by MOVPE technique on bulk GaN substrates and emitted light at the wavelength of around 420 nm. The effectiveness of the cavity suppression design was confirmed by measurements of high-resolution emission spectra. Further optimization was carried out by appropriate selection of the angles of the waveguide bend and the chip length. Thus; we succeeded in fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Group-III-Nitride-based superluminescent diodes (SLD) have received significant attention recently [13][14][15][16] owing to their unique features, which combine the advantages of both LEDs and LDs [17]. The short wavelength SLDs, have a broad spectral emission attributed to the coexistence of spontaneous and stimulated emission, known as amplified spontaneous emission (ASE) [18], making it a promising alternative for SSL-emitters.…”
Section: Introductionmentioning
confidence: 99%
“…Group-III-Nitride-based superluminescent diodes (SLD) have received significant attention recently [13][14][15][16] owing to their unique features, which combine the advantages of both LEDs and LDs [17]. The short wavelength SLDs, have a broad spectral emission attributed to the coexistence of spontaneous and stimulated emission, known as amplified spontaneous emission (ASE) [18], making it a promising alternative for SSL-emitters.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a passive absorber for suppressing lasing in a SLED is well known [9], [25], [26]. However, conventional (0001) GaN based devices differ from conventional (001) GaAs and InP based devices in that strong polarization (piezoelectric and spontaneous) effects induce strong electric fields within the QWs at zero applied bias [39].…”
Section: Broadband Gan Sledmentioning
confidence: 99%
“…Although various configurations of SLED design and cavity suppression have been proposed [9], limited work has been conducted on the practical use of absorbing section(s) in GaN SLEDs [25]. An absorbing section is electrically isolated from the light emitting section of a waveguide but is optically connected, with the absorbing section(s) ideally operated in loss.…”
mentioning
confidence: 99%
“…Table 1 summarizes the design and performance of the demonstrated GaN-based SLDs, comparing the emission wavelength, substrate material, configuration, waveguide design, and the maximum light output power reported in each case. 405 nm c-GaN "j-shape" waveguide curved ridge 350 mW (cw) [24] 408 nm c-GaN "j-shape" waveguide "j-shape" ridge 200 mW (cw) [25] 410 ~ 445 nm c-GaN tilted waveguide 2 µm ridge 30 ~ 55 mW (cw) [26] 420 nm c-GaN tilted facet 2 µm ridge 2 mW (cw) 100 mW (pulse) [27] 420 nm c-GaN "j-shape" waveguide AR/HR coating 3 µm ridge 200 mW (cw) [28] 439 nm m-GaN facet roughening 4 µm ridge 5 mW (pulse) [29] 443 nm c-GaN curved waveguide 2 µm ridge 100 mW (cw) [30] 445 nm c-GaN oblique facet 5 µm ridge - [31] 447 nm Semipolar GaN passive absorber 7.5 µm ridge 256 mW (cw) [17] 500 nm c-GaN curved waveguide 2 µm ridge 4 mW (pulse) [32] Since most of InGaN/GaN QW SLDs are grown on a polar, c-plane GaN substrate, there is a growing interest to develop high efficient violet-blue SLDs on nonpolar or semipolar substrates owing to a reduced polarization field presented in the QW structure [2]. Studies on semipolar and nonpolar GaN-based LEDs and LDs have revealed that the enhanced electron and hole wavefunction overlap is expected for InGaN/GaN QWs grown on nonpolar (m-plane) and semipolar GaN substrates, leading to an enhanced internal quantum efficiency [2,3].…”
Section: Introductionmentioning
confidence: 99%